A comparison of uncemented short versus standard stem length in total hip arthroplasty: results from the Dutch Arthroplasty Register - Mirthe H W van Veghel; Gerjon Hannink; Jakob van Oldenrijk; Liza N van Steenbergen; B Willem Schreurs (Acta Orthopaedica, 2023)
Background and purpose: We aimed to compare revision rates between uncemented short and standard stems in total hip arthroplasties (THAs) and the corresponding patient-reported outcome measures (PROMs). Patients and methods: We included all short (C.F.P., Fitmore, GTS, Metha, Nanos, Optimys, Pulchra, and Taperloc Microplasty) and standard stems in uncemented THAs registered between 2009 and 2021 in the Dutch Arthroplasty Register. Kaplan–Meier survival and multivariable Cox regression analyses were performed with overall and femoral stem revision as endpoints. Results: Short stems were used in 3,352 and standard stems in 228,917 hips. 10-year overall revision rates (4.8%, 95% confidence interval [CI] 3.7–6.3 vs. 4.5%, CI 4.4–4.6) and femoral stem revision rates (3.0%, CI 2.2–4.2 vs. 2.3%, CI 2.2–2.4) were comparable for short- and standard-stem THAs. Today’s predominant short stems (Fitmore and Optimys) showed short-term revision rates similar to that of standard-stem THAs. Other, less frequently used short stems had higher 10-year overall (6.3%, CI 4.7–8.5) and femoral stem (4.5%, CI 3.1–6.3) revision rates. Multivariable Cox regression also showed a higher risk for overall (HR 1.7, CI 1.0–2.9) and femoral stem revision (HR 2.0, CI 1.1–3.5) using the latter short stems compared with standard stems. An exploratory analysis of PROMs showed no difference. Conclusion: There was no overall difference in revision rates but a tendency toward increased revision of short stems both for the whole THA and for the stem itself. The less frequently used short stems had increased revision risk. No difference in PROMs was shown.